The incidence of radiologically verified community-acquired pneumonia requiring hospitalisation in adults living in southern Sweden, 2016-2018: a population-based study - Elisabeth Rünow; Frida Valeur; Gustav Torisson; Karin Hansen; Christian Theilacker; Kristian Riesbeck; Jonas Ahl (BMC Infectious Diseases)
Abstract Background Community-acquired pneumonia (CAP) was one of the most common causes of death in the European Union in 2017. Severity and mortality of CAP increase with age and an aging European population will require increased planning for prevention, control, and management of CAP. The purpose of this study was to provide an updated population-based estimate of the incidence of CAP requiring hospitalization in Northern Europe. Method We conducted a retrospective cohort study estimating the population-based incidence of CAP requiring hospitalization. Adults residing in Southern Sweden admitted between September 2016 and September 2018 with radiographically confirmed CAP and a primary discharge diagnosis consistent with pneumonia were identified by retrospective medical chart review. Incidence rates were stratified by age and sex. Results We identified 1,575 episodes of CAP in 1,471 unique individuals, accounting for 45% of the total eligible patient population. The crude incidence rate of CAP requiring hospitalization was 259 (95% CI: 246–272) and age-standardized rate was 294 (95% CI: 280–309) per 100,000 person-years. Among those aged 80 years and older, hospitalization rate was 17 times higher vs those aged 18–64 years, yielding an IRR 17.4 (95% CI: 15.4–19.7). Males aged ≥ 80 years had a 57% increased risk of CAP requiring hospitalization compared to women ≥ 80 years, resulting in an IRR of 1.57 (95% CI: 1.33–1.85). The lowest in-hospital case-fatality risk was among the 18–64 years group 3.4% (n = 16), and highest among those ≥ 80 years 8.1% (n = 46). Conclusion We found that the incidence and mortality of CAP requiring hospitalization in adults are considerable. Preventive measures are needed that target older adults and those at increased risk of CAP.